PKM Sosialisasi Penggunaan Aplikasi Canva Di Cynara's Corner - Rahmatika Rahmatika; Ulfa Pauziah; Ardhi Dinullah; Alqomari Cahyo (Jurnal Kabar Masyarakat, 2023)
Design Promotion of business in the current era of globalization has an important role in attracting consumers both products and services. Good product design will provide added value for businesses in promoting their products. In addition, an attractive product design will also provide a good profit for businesses because the product will be easily recognized. Design is also one of the components as a measure of the success of a marketing campaign whose goal is brand awareness or attracting the attention of potential buyers. A good product design will certainly increase online sales, compared to when you don't have a product design installed. By utilizing digital technology for promotions such as the many social media starting from Instagram, Facebook and even the marketplace. Of course, this is a great potential for online sellers to sell their products. The effort to provide a way to make product designs that are easy and attractive is to use a platform that can be used to load both desktop and mobile-based designs. One platform that is often used by business people is the Canva application, which offers templates that are readily available and free to create product designs. Cynara's Corner is a business actor in the fashion sector who has resellers to help market their fashion products, but not everyone understands and can operate the application, for that we want to socialize the use of the Canva application to increase reseller sales and help create attractive designs from photos existing product.